PEMBELAJARAN MATERI BANGUN RUANG SISI DATAR MENGGUNAKAN SOFTWARE CABRI 3D DI KELAS VIII SMPN 3 LANGSA - Nadya, B, A; Saiman; M, Zaki (Jurnal Dimensi Matematika, 2023)
Mathematics learning outcomes are one indicator of the effectiveness of mathematics learning. High mathematics learning outcomes indicate that the mathematics learning process is effective. The aim of this research is to find out that the learning outcomes of students taught using Cabri 3D software are better than the learning outcomes of students taught without using Cabri 3D software in class VIII_SMPN3 Langsa. This study uses a quantitative approach. The type of research used is true experimental design with Posttest Only Control Design. The population in this research is all students in class VIII of SMPN_3 Langsa for the 2023/2024 academic year, consisting of 11 classes with a total of 367 students. The sampling technique uses simple random sampling. So,the samples obtained in this research were class VIII-1 students with a total of 30 students and class VIII-2 students with a total of 30 students.The test used in this research is the description test. Based on the research results,the researcher tested the hypothesis in 2 ways,namely the manual method and using SPSS.The results obtained manually were the t_count value=6.688 and the t_table value=1.672 so that the t_count>t_tabel value=6.688>1.672. Then the data obtained from the Independent Sample_T-Test showed that the significant value(2-tailed sig)was 0.000. This value is smaller than 0.05(sig 0.000<0.05),so H0 is rejected and Ha is accepted. So,it can be concluded that the learning outcomes of students taught using Cabri 3D software are better than the learning outcomes of students taught without using Cabri 3D software in class VIII SMPN_3 Langsa.